2017
DOI: 10.1002/ceat.201700229
|View full text |Cite
|
Sign up to set email alerts
|

Start‐and‐Stop Operation of Fixed‐Bed Methanation Reactors – Results from Modeling and Simulation

Abstract: The production of synthetic natural gas (SNG) from renewable sources in cases requires a dynamic and intermitted operation of the methanation reactors. This may lead to catalyst damage. Therefore, the present work is aiming at identifying restrictions and optimization approaches of the start‐and‐stop operation of fixed‐bed methanation reactors. 2D modeling and simulation work is conducted and the warm‐start behavior of a fixed‐bed reactor after one to four hours operation intermittence is analyzed. The result … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 16 publications
(13 reference statements)
0
20
0
Order By: Relevance
“…Furthermore, the possibility of the reactor being able to restart due to its own thermal inertia and exothermicity of the reaction without requiring external heating was examined. [89] Simulations by Rönsch et al primarily identified a high temperature occurrence in dynamic operation of methanation reactors as a critical effect [90,91]. Kinetic modeling and simulation of methanation reactors has been reviewed in detail by Rönsch et al [92].…”
Section: Co 2 Methanation Under Dynamic Conditionsmentioning
confidence: 99%
“…Furthermore, the possibility of the reactor being able to restart due to its own thermal inertia and exothermicity of the reaction without requiring external heating was examined. [89] Simulations by Rönsch et al primarily identified a high temperature occurrence in dynamic operation of methanation reactors as a critical effect [90,91]. Kinetic modeling and simulation of methanation reactors has been reviewed in detail by Rönsch et al [92].…”
Section: Co 2 Methanation Under Dynamic Conditionsmentioning
confidence: 99%
“…Subsequently, the following investigations focused in detail on specific reactor types. Rönsch et al [ 65 ] studied the start and stop operation of an adiabatic methanation reactor. The goal was to identify the maximum standby time to allow for a warm and thus instantaneous restart of the reactor and hence for intermittent production patterns.…”
Section: Applicability Of Derived Definitionsmentioning
confidence: 99%
“…The goal was to identify the maximum standby time to allow for a warm and thus instantaneous restart of the reactor and hence for intermittent production patterns. [ 65 ] Matthischke et al [ 62 ] compared the startup behavior and the influence of the recycle ratio on different volume flows for different reactor types, namely an adiabatic and a cooled fixed‐bed reactor. The ability of methanation reactors to operate under different feed volume flows and compositions was proven via modeling studies.…”
Section: Applicability Of Derived Definitionsmentioning
confidence: 99%
“…The plant is based on a publication from Nonnen et al [6] describing experimental work on a zeolitic NaX heat storage system. Modifications and engineering predictions for the laboratory plant were derived with the help of a simulation model presented in [8,9]. The zeolites used in the plant are supplied by the commercial manufacturer Chemiewerk Bad Köstritz GmbH.…”
Section: Experimental Settingmentioning
confidence: 99%